THE IMPACT OF MONETARY POLICY TOWARDS CONVENTIONAL AND SHARIA FINANCIAL MARKET IN INDONESIA: (2010-2014) - Muhamad Fahri Akbar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The target of monetary economy is always how to influence the behavior of individual or firms in microeconomic and aggregate behavior in macroeconomic. Most of the discussion in microeconomic is on the function of money and interest rates in determining the behavior of individuals in using money either for investment or consumption. Therefore, monetary policy has the ability to influence the financial market. This paper tries to challenge the influence and impact of monetary policy towards the development of financial market especially when Indonesia has adopted two system in the economy which are sharia and conventional systems. By using VECM, the result indicates strong significant influence in both base money and interest rate in the long run towards these both financial markets. However, the impact of both monetary policies towards conventional financial market is contradictory with sharia financial market. In the short run, there is no contradictory of impact by monetary policy in regards of principle differences. Interst rate is insignificant towards all financial market but base money is significant only towards both sharia (JII) and conventional (IHSG) stock market but insignificant towards sukuk (SBIX) and conventional bond (VBIX) market. Keywords: Monetary Policy, Financial Market, Sharia and Conventional